Spirituality in higher education autoethnographies - Chang, Heewon, 1959-; Boyd, Drick. (Left Coast Press, Inc., 2011)
"This collection of articles explores how a wide range of academics-- diverse in location, rank and discipline-- understand and express how they deal with spirituality in their professional lives and how they integrate spirituality in teaching, research, administration, and advising. The contributors also analyze the culture of academia and its challenges to the spiritual development of those involved. Twenty chapter authors--from a variety of faith traditions--discuss the ways in which their own beliefs have affected their journeys through higher education. By using an autoethnographic, self-analytical lens, this collection shows how various spiritualities have influenced how higher education is understood, taught and performed. The book will stimulate debate and conversations on a topic traditionally ignored in academia"-- Provided by publisher.